Evaluation of student perspectives and awareness regarding Kenyir Geopark - Baharim Nor Bakhiah; Rahman Muhd Nur Ismail Abdul; Adriaysah Dony; Ali Mohd Afiq Mohd; Ariffin Effi Helmy; Atan Azrah (BIO Web of Conferences)
Kenyir Geopark, a National Geopark, showcases Malaysia’s diverse geology, rich biodiversity, and significant cultural heritage. This study surveyed public awareness of Kenyir Geopark, focusing on students to ensure the younger generation understands natural heritage. A questionnaire, developed and pilot-tested for clarity, included questions on demographics, awareness, information sources, extracurricular interest, and Earth science enjoyment. The survey was distributed at the “Program Jom Kenali Kenyir Geopark” at Sekolah Menengah Kebangsaan Jenagor, a partner school of Kenyir Geopark. Participants had 20 minutes to complete it, and data were analyzed statistically. The survey revealed that while 64.1% of students recognized Kenyir Geopark, only 11% frequently visited natural parks. Although they valued conservation, notable gaps in awareness and interest in earth sciences were identified. This highlights the need for improved educational programs to enhance student engagement and understanding of geopark activities. The proposed educational framework for Kenyir Geopark, which focuses on contextual learning, interactive tools, and collaborative teaching, cultivates a strong sense of ownership and responsibility among young people. Through immersive, hands-on experiences, this approach empowers them to actively participate in preserving and sustainably developing the park. By strengthening the connection between young people and Kenyir Geopark, these initiatives can promote long-term sustainability and community involvement in preserving this unique geological and cultural landscape.